Augmenting the learning experience in primary and secondary school education: a systematic review of recent trends in augmented reality game-based learning - Pellas, Nikolaos; Fotaris, Panagiotis; Kazanidis, Ioannis; Wells, David (Virtual reality : the journal of the Virtual Reality Society, 2019)
There is a significant body of research relating to augmented reality (AR) uses for learning in the primary and the secondary education sectors across the globe. However, there is not such a substantial amount of work exploring the combination of AR with game-based learning (ARGBL). Although ARGBL has the potential to enable new forms of teaching and transform the learning experience, it remains unclear how ARGBL applications can impact students’ motivation, achievements, and learning performance. This study reports a systematic review of the literature on ARGBL approaches in compulsory education considering the advantages, disadvantages, instructional affordances, and/or effectiveness of ARGBL across various primary and secondary education subjects. In total, 21 studies published between 2012 and 2017 in 11 indexed journals were analysed, with 14 studies focusing on primary education and 7 on secondary. The main findings from this review provide the current state of the art research in ARGBL in compulsory education. Trends and the vision towards the future are also discussed, as ARGBL can potentially influence the students’ attendance, knowledge transfer, skill acquisition, hands-on digital experience, and positive attitude towards their learning. This review aims to lay the groundwork for educators, technology developers, and other stakeholders involved in the development of literacy programmes for young children by offering new insights with effective advice and suggestions on how to increase student motivation and improve learning outcomes and the learning experience by incorporating ARGBL into their teaching.